IN VITRO PHOSPHORUS SOLUBILITY TEST OF DIFFERENT SOURCES OF PHOSPHORUS - A. Hifizah (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2011)
The solubility of P from different P supplements was measured with in vitro procedures, using three different tests, which were water solubility, citric acid solubility and acid (0.1M HCl) solubility. Water solubility and citrate solubility were common tests used by the fertiliser industry and acid solubility was a new test developed to mimic conditions within the digestive tract. There were five samples used: Lomon MDCP, Duchess RP, Kynofos, meat meal and MSOP. A separate test was done with the acid solubility test to examine the effect of time of incubation on inorganic P solubilised. The highest total P (%) was with Lomon MDCP (21.6%) and the lowest was in meat meal (5.5%). Duchess RP and meat meal had lowest solubility for all three tests. The statistical analysis showed that solubility depended on source of P and type of solution, with a significant interaction between P sources and type of solution (P<0.001). Solubility in 0.1M HCl increased with time incubated in all samples. Duchess RP and Meat Meal had lowest solubility at all time points but had reached 74 and 83% solubility respectively at 1 hr of incubation. pH value of all samples in acid solution ranged from 1.37 – 1.48. Solubility depended on source of P and time of incubation in 0.1M HCl with a significant interaction between P sources and time of incubation (P<0.001). The results indicated that all of the P sources used in this experiment were highly solubilised in dilute acid (0.1 M HCl) and so can be used as P supplements for animals if it is assumed that the 0.1 M HCl test mimics conditions within the digestive tract.